Leadership Renewal and Succession in Zimbabwean Political Parties: A Critical Analysis of Leadership Succession and Renewal Processes in ZANU-PF and the MDC-T - Chikerema A (Hilaris, 2023)
Political leadership in Africa vary from the “criminalization” of the state to political leadership as “ dispensing patrimony”, the “recycling” of elites and the use of state power and resources to consolidate political and economic power. Political parties just like any other organizations always need leadership renewal and revamping, besides ideological and policy renewal. Zimbabwean politics present a shunned leadership renewal as reflected by the two champion political parties namely ZANU PF and MDC-T. Despite hot political power contestation between MDC and ZANUPF, the parties` internal structures are hinged on the two Godfathers or Father figures that are Mugabe and Tsvangirai. They are the “labels “behind the two political parties. The suppressing of dissent voice on succession and renewal of leadership in the two parties has brew resistance from within and this has resulted in factional fights within the two political parties. The disgruntlement in the political parties has led to the stemming of the ‘bhoramusango concept’ from the electorate and party cadres whereby they are throwing or donating away their votes to other political parties. The ‘bhoramusango’ concept haunted ZANUPF in 2008 leading to its defeat by the opposition MDC-T. The paper takes the form of an analytic approach on leadership crisis in Zimbabwe. The narrative is framed on key concepts of leadership: namely leadership renewal and leadership succession, as agents operating within inherited structures negotiated political settlements, and form structures of leadership. Rulers gave priority to the consolidation of state power by installing party loyalists in the armed forces, civil service and local government. As part of this process, rulers have ensured consolidated power and authority.